Does managerial ability enhance earnings quality? The moderating role of corporate governance quality and ownership concentration - Romadhon, Fitri; Kusuma, Indra Wijaya (University of Islam Malang, 2020)
Earnings quality is information that can be determined by various factors, one of which is managerial ability. Thus, management quality itself can have a positive or negative impact on earnings quality, depending on the factors that affect their relationships. This study was conducted to reexamine the effect of managerial ability on earnings quality by including corporate governance quality and ownership concentration as factors that are expected to be able to explain the inconsistencies in the results of previous studies. This study used the data of manufacturing companies listed on the Indonesia Stock Exchange in 2010-2016 as study sample with total observations were 253. The analysis technique used for hypothesis testing was a multiple linear regression analysis. This study succeeds in proving the moderation role of governance quality in strengthening the relationship between managerial ability and earnings quality. However, the role of ownership concentration as moderator factors failed to prove in this study. Interestingly, there is a negative effect between managerial ability and earnings quality. The opportunistic actions taken by managers who want to meet their performance targets was considered as the reason of the negative effect between managerial ability and earnings quality.